2020
DOI: 10.1016/j.surg.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Association between insurance cost-sharing subsidy and postoperative opioid prescription refills among Medicare patients

Abstract: Background: Models of health care coverage with varying degrees of patient cost-sharing have been shown to influence health care behaviors for chronic conditions including medication adherence. The effect of insurance cost-sharing subsidies on the probability of postoperative opioid refill, however, is unclear.Methods: This retrospective cohort study examined 100% Medicare claims data among patients (N = 21,781) ages 65 and older undergoing orthopedic procedures in Michigan between January 2013 and September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Full cost sharing of opioid medication received by low-income patients has an impact on opioid refilling habits compared to patients receiving partial subsidies (25), These results are consistent with previous findings showing that decreased cost sharing was associated with increased drug replenishment (14).…”
Section: Pharmacysupporting
confidence: 90%
See 1 more Smart Citation
“…Full cost sharing of opioid medication received by low-income patients has an impact on opioid refilling habits compared to patients receiving partial subsidies (25), These results are consistent with previous findings showing that decreased cost sharing was associated with increased drug replenishment (14).…”
Section: Pharmacysupporting
confidence: 90%
“…Based on the 8 articles reviewed, it was found that insurance financing schemes can affect the demand and supply of drugs. Low premium insurance and subsidies for full health coverage will increase demand for medicines (8,14). Health insurance financing by implementing cost sharing or co-payment will reduce the demand or need for drugs, because patients have to pay for part of the total health financing themselves (5,12,13,(15)(16)(17).…”
Section: Pharmacymentioning
confidence: 99%
“… 42 While it is important to consider other socioeconomic confounders as potential contributors to these findings as well as the consequences of out-of-pocket costs and cost-sharing for opioid use, our study suggests that Medicaid patients remain at higher risk for opioid-related harms compared with patients with other payer types despite considerable improvement in opioid outcomes during the study period. 43 , 44 , 45 , 46 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to adult literature suggesting that opioid prescriptions are higher in lower‐income people 27,28 . Possible explanations are that providers have a more comprehensive discussion about risks of opioids with higher income parents and may prescribe these families a small quantity of opioids “just‐in‐case.” Another explanation could be that lower income families could not afford to fill prescriptions 29 . Hispanic patients were less likely to receive opioids and when they did, received smaller quantities.…”
Section: Discussionmentioning
confidence: 99%